The Mediterranean Sea - Saliot, Alain; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
Our current knowledge on chemicals in the Mediterranean Sea is presented. The increasing rates of exploitation and pollution are producing unprecedented environmental changes in this semi-enclosed sea, which is often considered a unique model to study global change evolution of our ocean and coastal seas. This volume deals with several aspects of the chemical contamination of the Mediterranean Sea and its health. After a description of the general physical and socio-economic context, exploration of processes governing the fate of chemicals, the budget of both inorganic and organic major and preoccupant contaminants and a description of new tools to study the impact of pollution on the Mediterranean Sea are discussed. The book serves as a reference source for the chemical aspects of the Mediterranean Sea for students and scientists and a practical guide for those who have professional responsibility for the management and operation of environmental impact assessment programmes.
Lucien LAUBIER: Mediterranean Sea and Humans: improving a Conflictual Partnership -- Claude MILLOT and Isabelle TAUPIER-LETAGE: Circulation in the Mediterranean Sea -- J.P. BETHOUX: Nutrient (N,P,Si), Oxygen (O2) and Carbon Ratios, CO2 Sequestration and Anthropogenic Forcing in the Mediterranean Sea -- Joan ALBAIGES: Persistent Organic Pollutants in the Mediterranean Sea -- Christophe MIGON: Trace Metals in the Mediterranean Sea. Daniel COSSA: The Mediterranean Mercury Anomaly, a Geochemical or a Biological Issue -- Françoise ELBAZ-POULICHET: River Inputs of Metal and Arsenic -- Stefano GUERZONI: Input of Various Chemicals Transported by Saharan Dust and Depositing at the Sea Surface in the Mediterranean Sea -- Bozena COSOVIC: Surface Active Properties of the Sea Surface Microlayer and Consequences for Pollution in the Mediterranean Sea -- Jean-François RONTANI: Importance of Visible Light-induced Photooxidation Processes in the Mediterranean Sea -- Michael O. ANGELIDIS: Exchange of Pollutants (trace elements) at the Sediment Boundary -- Hervé THEBAULT: Biological Indicators in Mediterranean Coastal Waters : a Link between Environmental Chemistry and Ecological Assessment -- Jean-Marie BECKERS: Applicability of Models in the Field of Environmental Chemistry of the Mediterranean Sea -- Vittorio BARALE: Satellite Observations as Indicators of the Health of the Mediterranean Sea.
Keywords: Water pollution; Water quality; Environmental management; Environmental pollution; Geoecology; Environmental geology; Oceanography; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Water Quality/Water Pollution; Environmental Management; Terrestrial Pollution; Geoecology/Natural Processes; Oceanography